Pembinaan Mutu Guru melalui Program Penilaian Kinerja Guru (PKG) di SMK Negeri 1 Sangatta Utara - Khusnul Wardan (Al-Rabwah, 2020)
From the exposure to the results of the interview, it can be concluded about the implementation of Teacher Performance Assessment (PKG) at SMK Negeri 1 Sangatta Utara as follows: First, the implementation of PKG by the principal and assistant has been going well, this is illustrated from the results of observations and interviews in the field of all interviewees who were asked answered that they had been in PKG by the principal and assessors from the element of senior teachers. In principle, teachers are happy in PKG because PKG is a part of the teacher quality development program. From the implementation of the PKG, the teacher knows the location of the advantages and disadvantages in carrying out tasks within one academic year. Second, based on data in the field, there are still many teachers who do not know what components are assessed by the school principal in implementing PKG. The teacher assumes that PKG is the same as the implementation of supervision, which is what is assessed by the learning device and process. Supervision is part of the PKG because the implementation of the PKG also requires class visits by the principal to find out how teachers teach. To provide an understanding that informs teachers about the implementation of the PKG and what components are being assessed, the principal needs to socialize to the teacher about what components are assessed in the implementation of the PKG. This socialization needs to be done so that teachers have the same perception of the implementation of PKG by the school principal. Third, the principal needs to evaluate the PKG implementation that has been implemented. This evaluation aims to determine the extent of the success of the PKG implementation and the contribution of PKG to improving the quality of teachers at SMK Negeri 1 Sangatta Utara. Things that need to be evaluated include planning the PKG, organizing the PKG, implementing the PKG. The school principal needs to involve and invite discussion of the components involved in implementing the PKG.